Temperature Control Using Labview-Based Fuzzy Logic on a Calorimeter for Physics Experiments - Yulian Zetta Maulana; Ivan Muhtarom (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
In this research, an analysis of temperature regulation was conducted on the calorimeter used for Physics practicum using the Labview controller. The purpose of this study is to obtain a stable calorimeter temperature output so that it makes it easier for the practicum to be carried out. The object to be measured is the output temperature of the calorimeter which is heated and detected by the LM-35 temperature sensor. NI-DAQ USB 6008 is used as the data acquisition device, and is connected to Labview software. The data collection process was carried out by comparing 5 tests, including testing without a Fuzzy controller, testing a Fuzzy controller with 74 percent, 80 percent, 89 percent, 90 percent from PWM maximum defuzzification. The final results show that temperature regulation on the calorimeter with Fuzzy logic is quite effective with 90 percent defuzzification, because the temperature can reach the set point value with a settling time of 40 minutes and has a steady state error of 1.1 percent.